Reale, Pensiero, Linguaggio: una configurazione del problema della verità - Panizzoli, Francesco (Rivista Italiana di Filosofia del Linguaggio)
Following the suggestion of Wittgenstein (1922: 24.9.1914), We propose a configuration of a possible “coordination of relations”, which form a specify structure of the truth. We use the modal logic triadic relation named euclidean, between three terms that we interpret how three fundamental dimensions of being (esse): Real, Thought and Language. Euclidean relations between these dimensions configure a specify structure of the truth.